INFRARED MULTIPLE PHOTON EXCITATION AND DISSOCIATION OF SIMPLE MOLECULES - Ashfold, M; Hancock, G; Ketley, G (1979)
The collisionless multiple photon dissociation of CH3NH2 by a pulsed CO2 laser to produce NH2 radicals has been shown to be dependent upon the laser intensity. Measurements have been made of the fluence dependences of the dissociation yields at various times during CO2 laser pulses for three laser wavelengths overlapping different regions of the low intensity i.r. absorption spectrum of CH3NH2. In all cases, for a given fluence, dissociation is more efficient when that fluence is delivered in the shortest time, i.e., a higher average intensity. These effects are more prominent near the peak of the CO2 pulse than in the tail, although relatively more dissociation takes place during the tail of the pulse. The results are discussed with respect to recent theoretical predictions of intensity dependences, and a model of the absorption process is suggested in which molecules are initially prepared for further absorption in an intensity dependent step by the high intensity peak of the CO2 laser pulse. Variations of dissociation yield with laser wavelength largely reflect the relative efficiencies with which the laser peak prepares molecules in vibrationally excited states for subsequent absorption and dissociation.